PCK1 Downregulation Promotes TXNRD1 Expression and Hepatoma Cell Growth via the Nrf2/Keap1 Pathway - Tuo, Lin; Xiang, Jin; Pan, Xuanming; Gao, Qingzhu; Zhang, Guiji; Yang, Yi; Liang, Li; Xia, Jie; Wang, Kai; Tang, Ni (Frontiers in Oncology, 2018)
Gluconeogenesis, generates glucose from small carbohydrate substrates and drives the metabolic flux in parallel but opposite to glycolysis. The cytoplasmic isoform of phosphoenolpyruvate carboxykinase (PCK1 or PEPCK-C), a rate-limiting enzyme in gluconeogenesis, initiates the gluconeogenesis process and is reportedly dysregulated in multiple types of cancer. Gluconeogenesis mainly occurs in the liver during fasting, and previous studies have demonstrated that PCK1 acts as a tumor suppressor in hepatocellular carcinoma (HCC); however, the role of PCK1 in cancer progression remains incompletely understood. In the current study, we found that PCK1 expression was decreased in HCC as compared to adjacent normal liver tissues, and low PCK1 expression correlated with poor patient prognosis. Furthermore, overexpression of PCK1 suppressed reactive oxygen species (ROS) production and nuclear translocation of Nrf2 in hepatoma cells. In addition, thioredoxin reductase 1 (TXNRD1), an antioxidant enzyme regulated by the Nrf2/Keap1 pathway, was downregulated upon overexpression of PCK1 in HCC cell lines. Furthermore, we verified this axis using nude mouse xenograft model. Finally, we found that auranofin, a TXNRD1 inhibitor, enhanced the sensitivity of PCK1-knockout hepatoma cells to sorafenib-induced apoptosis. Taken together, our findings suggest that PCK1 deficiency promotes hepatoma cell proliferation via the induction of oxidative stress and the activation of transcription factor Nrf2, and that targeting the TXNRD1 antioxidant pathway sensitizes PCK1-knockout hepatoma cells to sorafenib treatment in vitro.